THE RESEARCH RESULTS OF TENDER PROCUREMENTS OF THE DRUGS FOR CANCER PATIENTS IN UKRAINE - Panfilova, G. L.; Tsurikova, O. V. (Zaporozhye Medical Journal, 2014)
Introduction. Since 2002, the pharmaceutical care of the cancer patients in Ukraine is carried out centrally by public funds in the framework of the target program "Oncology." In a chronic shortage of funds in the national health care system, as well as taking into account the perspectives of the introduction of the social model of obligatory medical insurance (OMI), enhanced the importance of research on the development of rational mechanisms for the use of public funds, which are sent to drug purchases. Given the high mortality rate among cancer patients, especially in children in Ukraine, these works are of particular socio-economic importance. The aim of work. To study drug purchases that are made for cancer patients in Ukraine in order to identify the main problems and directions of rational scientific basis for the use of public funds in terms of lack of resources in health care, as well as from the perspectives of the introduction of the social model of OMI in Ukraine. Materials and methods. Objects of research: data from the National Cancer Registry, annual plans and registers of public drug procurement Ministry of Ukraine. The paper used data from national legislative and regulatory framework governing the organization of pharmaceutical support cancer patients, standard methods of statistical processing of the dynamics of the clinic-economic analysis. Results and discussion. During 2010-2013 marked increase in the amounts of permanent drug purchases for cancer patients, which is on the growth rate did not meet the dynamics of changes in the relevant during epidemiological indicators. The results integrated ABC/VEN-analysis found no drug purchasing products from the group N and with the status A/V, and the dominance of the number of agents with the status items C/V. The main volume of financial resources was directed to the purchase of drugs from the group E (84.8% - 92.4%) and the status of A/E (78,9% -79,8%), as well as drug belonging to the group L01X - Other antineoplastic agents, (64.8% - 72.4%). During 2010-2013 there is a significant proportion of the fluctuation of the value of the groups of drugs В (in the status В/V and В/E), V (in the status В/V and C/V), E (in the status В/E and C/E). This indicates a lack of evidence-based approaches to determining the need for the acquisition and purchase volumes for the budget. In addition, the statutes disproportionately relative to all groups of oncohematological patients, the distribution of funds for the procurement of drugs. Stable priority position on the amount of purchases (63.5% - 71.2%) took five drugs (bortezomib 3.5 mg, imatinib 400 mg, nilotinib 200 mg, rituximab 500 mg, fludarabine 50 mg), which in most cases, are used in the treatment of chronic forms of leukemia and lymphoma. Conclusions. The results of these studies provide an opportunity to argue about the need to develop and implement the state target program "Hematology." The most important condition for the effective implementation of this program in the functioning of the social model is the introduction of OMI of evidence-based model provide pharmaceutical oncohematological patients according to their actual needs in the various denominations of drugs, as well as the financial capacity of the national health system.